Respuesta :

Answer:

[tex]4\sqrt{2b}[/tex]

Step-by-step explanation:

[tex]\sqrt{98b}-\sqrt{72b}+\sqrt{18b}[/tex]

Apply radical rule [tex]\sqrt{ab} =\sqrt{a} \sqrt{b}[/tex]:

[tex]\implies \sqrt{98}\sqrt{b} -\sqrt{72}\sqrt{b} +\sqrt{18}\sqrt{b}[/tex]

Factor out common term [tex]\sqrt{b}[/tex]:

[tex]\implies \sqrt{b}(\sqrt{98} -\sqrt{72}+\sqrt{18})[/tex]

Rewrite 98, 72 and 18:

[tex]\implies \sqrt{b}(\sqrt{49 \cdot 2} -\sqrt{36 \cdot 2}+\sqrt{9 \cdot 2})[/tex]

[tex]\implies \sqrt{b}(\sqrt{49}\sqrt{2} -\sqrt{36}\sqrt{2}+\sqrt{9}\sqrt{2})[/tex]

[tex]\implies \sqrt{b}(7\sqrt{2} -6\sqrt{2}+3\sqrt{2})[/tex]

Factor out common term [tex]\sqrt{2}[/tex]:

[tex]\implies \sqrt{b}\sqrt{2}(7 -6+3)[/tex]

[tex]\implies \sqrt{b}\sqrt{2}(4)[/tex]

[tex]\implies 4\sqrt{2b}[/tex]